(3GdJUOjQ GdeYGUQ hGdJMGdaGJ GdGSJQGJjLjI (B/s - (3GdfLGQ, aQjOs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2008)
(3GdMQhH GdJLGQjI GdeYGUQI ,ETcGdjI GdJUOjQ GdYQHj , GdYhdeI hJMOjGJ GdJUOjQ , GdGWGQ GdYGe dJShjb GdUGOQGJ GdYQHjI , GdJfGaSjI haQU GdJUOjQ GdLOjOI GdGOGQI GdGSJQGJLjI ddJUOjQ EYOGO hJfejI GdHQGeL GdJUOjQjI GdeJcGedI EJaGbjGJ GdJeKjd GdJLGQj hbSe GdefGRYGJ GdJUOjQjI , HMhK GdJShjb GdOhdj ddUGOQGJ , JMOjO GdehGUaGJ GdfeWjI ddUGOQGJ , Sdhc GdeSJgdc GdOhdj , Jejd GdUGOQGJ , OhGaY GdJMGdaGJ GdGSJQGJLjI ddJUOjQ , GdeTGQcI aj CQHGM GdJMGdaGJ GdJLGQjI , GdJMGdaGJ GdJLGQjI GdGbJUGOjI hEOGQI GdCYeGd GdOhdjIs
(3HjHdjhZQGajG U(B.443 (3edGMb U(B. 365s
Keywords: (3HMhK GdJShjbs; (3JUOjQs; (3JfGaSs